PENINGKATAN KEMAMPUAN NUMERASI PERKALIAN MELALUI MEDIA PAPER PADA SISWA KELAS III SD 4 BULUNGCANGKRING - Affan Uyung Al Farichy; Lovika Ardana Riswari; Rihayati (STKIP Subang, 2025)
This classroom action research aims to improve students' numeracy skills in understanding the concept of multiplication of whole numbers 1 to 10 through the use of PAPER media